THE EFFECT OF OWNERSHIP STRUCTURE ON OCCUPATIONAL SAFETY AND HEALTH DISCLOSURES - Fathurohman, Muhammad Agiansyah; Savitri, Sekar Ayu Dimas; Jubaedah, Siti (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This study aims to determine and analyze the effect of ownership structure on occupational safety and health disclosure in mining companies listed on the Indonesia stock exchange in 2020 - 2022 through the perspective of stakeholder theory. Design/methodology/approach: The research method uses a quantitative approach with secondary data totaling 54 annual reports obtained using purposive sampling technique and data analysis techniques using multiple linear regression. Findings: This study shows that foreign ownership and managerial ownership have significant positive influence on occupational safety and health disclosure, while institutional ownership has no influence. Practical implications: The results of this study can be a consideration for the management of the company to design what is the right strategy regarding how the management maximizes the value of the company which will indirectly increase the benefits of managers who are also owners of the company. Originality/value: This research is able to explain the factors that influence accupational safety and healt disclosure Paper type: Research paper